Caligus coryphaenae infection from the Osumi strait, Southern Japan: A new record on wild yellowtail (Seriola quinqueradiata). - Khoa, T.N.D. & F. Shaharom-Harrison (Veterinary Parasitology: Regional Studies and Reports, 2021)
The caligid parasite Caligus coryphaenae has been reported in several marine fishes from Japan. In this study, a total of 223 wild yellowtail (Seriola quinqueradiata) were collected from Kagoshima fish market, separated into three groups according to total length (TL 70 cm), and examined for C. coryphaenae infection. A total of 518 specimens of C. coryphaenae were isolated giving an overall prevalence of infection and mean intensity of 24.2% and 4.7 ± 3.5, respectively. Body surface, fins and operculum of hosts TL > 50 cm were recorded as preferred sites for the attachment of C. coryphaenae. Of female specimens, 56.7% bore egg strings with various egg string lengths (7.1 ± 1.2 mm), carrying from 98 to 140 eggs (0.06 ± 0.005 mm in length) per each string. To our knowledge, this is the first report of C. coryphaenae infection from wild yellowtail in Japanese waters and globally. This parasite has not been reported in yellowtail culture to date, but the finding on wild specimens of yellowtail means that it poses a risk to their culture.